THE INFLUENCE OF PRODUCTIVE ZAKAT UTILIZATION ON WELFARE FROM THE MAQASHID SYARIAH PERSPECTIVE WITH EMPOWERMENT AS A MEDIATING VARIABLE - Izzah Dienillah (JURNAL PROFIT, 2026)
It was observed that the poverty rate in Bondowoso Regency declined from 2020 to 2024, indicating that poverty has gradually been alleviated and community welfare has improved. This study aims to: (1) analyze the direct effect of productive zakat utilization by the National Zakat Agency (BAZNAS) of Bondowoso Regency on the welfare of MSMEs from a maqashid sharia perspective; (2) examine the direct effect of BAZNAS empowerment on MSME welfare from a maqashid sharia perspective; and (3) analyze the indirect effect of productive zakat utilization on MSME welfare from a maqashid sharia perspective, with BAZNAS empowerment serving as a mediating variable.This study employed a quantitative research approach with an explanatory design. The population included 130 mustahik (zakat beneficiaries). Using the Isaac and Michael table with a 5% margin of error, a sample of 95 respondents was chosen through purposive sampling. Data collection involved observation, documentation, and questionnaires. The data were analyzed using Partial Least Squares (PLS). The findings indicate that productive zakat utilization has a significant positive effect on MSME welfare from a maqashid sharia perspective. However, BAZNAS empowerment in Bondowoso Regency does not have a significant effect on MSME welfare from a maqashid sharia perspective. In addition, productive zakat utilization has a significant effect on BAZNAS empowerment. Nevertheless, productive zakat utilization does not have an indirect effect on MSME welfare through BAZNAS empowerment as a mediating variable. Keywords: Productive Zakat Utilization, Welfare, BAZNAS Empowerment, and Maqashid Sharia